Uncovering the Structural Diversity of Y(III) Naphthalene-2,6-Dicarboxylate MOFs Through Coordination Modulation - Griffin, Sarah L.; Wilson, Claire; Forgan, Ross S. (Frontiers in Chemistry, 2019)
Metal-organic frameworks (MOFs) – network structures built from metal ions and clusters and connecting organic ligands – are typically synthesized by solvothermal self-assembly. For transition metal based MOFs, structural predictability is facilitated by control over coordination geometries and linker connectivity under the principles of isoreticular synthesis. For rare earth MOFs, coordination behaviour is dominated by steric and electronic factors, leading to unpredictable structures and poor control over self-assembly. Herein we show that coordination modulation – the addition of competing ligands into MOF syntheses – offers programmable access to six different Y(III) MOFs all connected by the same naphthalene-2,6-dicarboxylate ligand, despite controlled synthesis of multiple phases from the same metal-ligand combination often being challenging for rare earth MOFs. Four of the materials are isolable in bulk phase purity, three are amenable to rapid microwave synthesis, and the fluorescence sensing ability of one example towards metal cations is reported. The results show that a huge variety of structurally versatile MOFs can potentially be prepared from simple systems, and that coordination modulation is a powerful tool for systematic control of phase behaviour in rare earth MOFs.